(untitled) (Innovative professional education, 2023)
Given the current state of the construction industry and the catastrophic environmental situation in post-war Ukraine, the professional training of future construction workers should focus on enhancing cognitive activity, environmental education, and responsibility for the consequences of professional activity. The developed eco-oriented pedagogical technologies, in particular the technology of problem-based learning, information and communication technologies, and project-based learning, are appropriate and effective in this process.